Sources of Chinese tradition - De Bary, Wm. Theodore, 1919-2017.; Bloom, Irene; Chan, Wing-tsit, 1901-1994.; Adler, Joseph; Lufrano, Richard John, 1952- (New York : Columbia University Press, 1999)
Second edition of an anthology of primary sources on Chinese history features new translations of more than half the works which appeared in the first (1960) edition, and adds new selections as well. Texts are arranged chronologically, with this volume spanning from the earliest literate Chinese societies through the 17th century Ming dynasty. The book, and each individual chapter, features an introduction by the editors contextualizing the material. Annotation copyrighted by Book News, Inc., Portland, OR
vol. 1. From earliest times to 1600 -- vol. 2. From 1600 through the twentieth century
Vol. 2 compiled by Wm. Theodore De Bary and Richard Lufrano
Includes bibliographical references and index
Keywords: China -- Civilization -- Sources; Reference works